Reconstruction of the Concept of Qur’anic Education: A Philosophical Analysis of the Meanings of Tarbiyah, Ta’lim, and Tazkiyah - Umayyatun; Afandi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to reconstruct the concept of Qur’anic education through a philosophical analysis of tarbiyah, ta’lim, and tazkiyah. This research employs a library research approach with philosophical and thematic exegesis (maudhu’i), utilizing the Qur’an, classical and contemporary tafsir, and recent scholarly literature (2023–2026). Data were analyzed using content analysis and philosophical interpretation. The findings show that tarbiyah represents a holistic process of nurturing human potential, ta’lim functions as knowledge transmission and epistemological development, and tazkiyah emphasizes spiritual purification and moral formation. These concepts are integratively interconnected and form a comprehensive system of Islamic education encompassing ontological, epistemological, and axiological dimensions. The novelty of this study lies in integrating these three concepts into a unified philosophical framework, addressing previous fragmented approaches. The study contributes theoretically by strengthening the integrative paradigm of Islamic education and practically by providing a foundation for curriculum development. This study concludes that integrating tarbiyah, ta’lim, and tazkiyah is essential to produce individuals who are intellectually competent, spiritually grounded, and morally upright.